1926
DOI: 10.1136/bmj.2.3418.59-a
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Absence of the Pectoral Muscles

Abstract: PINNING THT YJDAR STYLOIP PROCESS tIN~'COLLES'S FRA.CTURE. [ THE BRITISV 59 I.EIA JULA are not already closed by the disease. Sodium bromide was at first tried instead of lipiodol, but it was founid that it was very apt to soak the wool and escape. It is also as wteOl to alpply a piece of wet wool to the puacture lhole in the indferior rneatus as sooni as the needle has beeni removed, to p)revellt escape of lipiodol in this situation. Thie lipiodol may be remnoved with the Watson-Williams syringi,e, the needle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 0 publications
1
12
0
1
Order By: Relevance
“…Bing cited the frequency of pectoral muscle anomalies at approximately 1 of 11,000 cases, but suggested that it may be an overestimation relative to other muscle anomalies because this malformation is more easily observed than other muscular defects. Adding to this number of cases, Wendel in 1905 (reviewed by Jones, 1926) reported on 70 cases that generally confirmed Bing's findings, and included the first report of bilateral pectoral muscle defects. Clark revisited the literature in 1915 and reported the number of cases of pectoral muscle defects to be 202.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…Bing cited the frequency of pectoral muscle anomalies at approximately 1 of 11,000 cases, but suggested that it may be an overestimation relative to other muscle anomalies because this malformation is more easily observed than other muscular defects. Adding to this number of cases, Wendel in 1905 (reviewed by Jones, 1926) reported on 70 cases that generally confirmed Bing's findings, and included the first report of bilateral pectoral muscle defects. Clark revisited the literature in 1915 and reported the number of cases of pectoral muscle defects to be 202.…”
Section: Discussionsupporting
confidence: 51%
“…The combination of a lack of the pectoralis major and/or minor muscles with skeletal, vascular, and surface feature anomalies in the ipsilateral upper limb has been referred to as Poland's syndrome. Poland's syndrome is the most common condition in which pectoral muscle anomalies are noted, with a prevalence of approximately 1 in 20,000 live births (Jones, 1926). Our case does not constitute Poland's syndrome because of the lack of accompanying skeletal or vascular deficits.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…El SP es más com�n en hombres �ue en mujeres y es más frecuente en el lado derecho �ue en el iz�uierdo [1][2][3] . La definición antigua de SP incluía la combinación de la ausencia o hipoplasia de los m�sculos pectoral mayor y�o menor con anomalías es�ueléticas, cutáneas y subcutáneas en el hemitórax ipsilateral y grados variables de defectos en las extremidades superiores.…”
Section: Discussionunclassified